Assessment Of Financial Performance At PT Kimia Farma Tbk With A Financial Ratio Approach For The Years 2022-2023 - Ilham, Ahmad; Wulan Cahya Ningrum; Erwin Budianto (Al Tijarah, 2025)
The pharmaceutical industry plays an important role in the healthcare sector, but financial challenges can hinder its sustainability. PT Kimia Farma Tbk experienced a decline in financial performance, characterized by increasing losses and dependence on debt. This study aims to analyze the company's financial performance in 2022-2023 using profitability, liquidity, solvency, and activity ratios. The method used is descriptive quantitative analysis based on the company's financial statements. The results showed negative profitability, with declining ROA and ROE, low liquidity with Current Ratio and Cash Ratio below industry standards, and increasing DAR and DER, reflecting high dependence on debt. These results confirm the need for asset optimization strategies and operational efficiency. Further studies can explore the influence of external factors on the company's financial performance.Financial Performance, ROA, ROE, Current Ratio, Cash Ratio, DAR, DER, WCTO, TATO.